2020
DOI: 10.1515/chem-2020-0124
|View full text |Cite
|
Sign up to set email alerts
|

Citrullus colocynthis (L.) Schrad: Chemical characterization, scavenging and cytotoxic activities

Abstract: Citrullus colocynthis (L.) Schrad (C. colocynthis) called colocynth is a wild species that belongs to the family cucurbitaceae. The present research work aimed to study the phytochemical composition, cytotoxic and antioxidant activities of C. colocynthis seed extract. The chemical characterization of C. colocynthis seeds was effectuated using a gas chromatograph coupled to a mass spectrometer (GC-MS). The cytotoxic activity of C. colocynthis seed extract against breast cancer cell lines (MDA-MB-231) and colon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The pharmacological activities investigated in this study are frequently related to the identified compounds in the C. colocynthis seed extract since the chemical analysis showed many potentially bioactive compounds with pharmacological activities, including antioxidant and antibacterial activities as reported in earlier works [30][31][32][33][34][35]. In this sense, Jasmonic acid played a crucial role in defense against insects, pathogenic microorganisms, kin aging, as well cancer development [36,37].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The pharmacological activities investigated in this study are frequently related to the identified compounds in the C. colocynthis seed extract since the chemical analysis showed many potentially bioactive compounds with pharmacological activities, including antioxidant and antibacterial activities as reported in earlier works [30][31][32][33][34][35]. In this sense, Jasmonic acid played a crucial role in defense against insects, pathogenic microorganisms, kin aging, as well cancer development [36,37].…”
Section: Discussionmentioning
confidence: 54%
“…In this sense, the differences can be attributed to solvent polarities used for extraction. The antibacterial activity could probably due to the presence of cucurbitacin molecules since the cucurbitacin E was effective against M. tuberculosis H37Rvat [32].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Using CC fruits and seeds extracts was reported to alleviate the oxidative stress by increasing SOD and GHS-Px activities, while decreasing the MDA levels in the induced-Parkinson'sdiseased mouse model [46]. The presented positive impact of CCs supplementation on redox status to heat-stressed broilers can be contributed to its antioxidant compound contents (e.g., α-tocopherol, γ-tocopherol, β-carotene, phenolic acid and flavonoids) [18,42,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Cucurbitacin B, E, and I, among the most potent components of C. colocynthis seed, have been shown to have antibacterial action against Staphylococcus aureus, Bacillus cereus, and K. pneumonia (Ali et al 2013). Cucurbitacin E has also been shown to have antibacterial properties against M. tuberculosis H37Rvat (Bourhia et al 2020). The biological activity of plant extracts is dependent on the solvent and extraction method used, and the antimicrobial effectiveness of plant extracts is dependent on the active substances, selected bacterial strains, and plant parts tested,so antimicrobial activity may differ from one bacterium gram negative to another gram positive (Qaralleh et al 2019).…”
Section: Discussionmentioning
confidence: 99%